Interactive dental health education on the knowledge level of little doctors students of Muhammadiyah 4 Elementary School - Sitalaksmi, Ratri Maya; Kartikasari, Nadia; Mundiratri, Karina; Lestari, Kurnia Ayu; Atikasari, Nurani; Gunawan, Hendri Budi; Setiawan, Panji Adhytama Pragana; Charyadie, Arlita Gladys Tricia; Utami, Firdha Putri; Aldrian, David; Batul, Fatimah (Indonesian Journal of Dental Medicine, 2024)
Background: Dental and oral health education is conducted with the aim of changing the habits of a person, group of people, or society so they can gain knowledge, attitudes, and habits to behave in a healthy way in the field of dental and oral health. Elementary school age is the right time for teachers to introduce and instill healthy living habits. A dental and oral health education for Little Doctor students is assumed to help improve the dental and oral health of other students, teachers, and other staff of the school, as well as the people around the student outside of school. Purpose: To describe the effect of interactive dental health education on knowledge improvement. Methods: This study’s sample size was 31 Little Doctor students in the third through sixth grades. The activity in general adopted two-way communication; interactive speaking was performed to stimulate the students attentiveness to the topics, allowing students to engage with the speakers. To assess the students’ knowledge level of oral and dental health, a pre-test questionnaire was filled out prior to starting, and the same questionnaire was filled out as a post-test after completing all the agenda. Results: There were significant differences between pre-test and post-test results (P-value < 0.05), with the mean rank of the post-test group (45.56%) being significantly higher than the pre-test group (17.44%). Conclusion: The interactive education method in elementary school was found to be efficacious and more preferable as it matches the level of growth and development in school-age children.